Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/cbic.201700420
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Approach to Biological Safety: Molecular‐Level Control of an Integrated Zinc Finger Nuclease

Abstract: Application of artificial nucleases (ANs) in genome editing is still hindered by their cytotoxicity related to off‐target cleavages. This problem can be targeted by regulation of the nuclease domain. Here, we provide an experimental survey of computationally designed integrated zinc finger nucleases, constructed by linking the inactivated catalytic centre and the allosteric activator sequence of the colicin E7 nuclease domain to the two opposite termini of a zinc finger array. DNA specificity and metal binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
(90 reference statements)
1
4
0
Order By: Relevance
“…Under these conditions, the supercoiled DNA changed to open circular form at 24 h. After a further increase of the metal ion concentration, at 1:2 protein-to-Zn 2+ molar ratio, the catalytic activity is completely inhibited. Our previous studies showed that the CD spectra of apo NColE7 shifted slightly upon binding the Zn 2+ ion, as a consequence of minor changes in the solution structure [73] and the addition of Zn 2+ ions to N4-ZF-C105 AN resulted in a spectral shift, similar to that observed for NColE7 itself [77]. The above cataytic results using C45-ZF-N85 are in agreement with these observations.…”
Section: Plasmid Cleavage Activity Of the C45-zf-n85 Artificial Nucleasesupporting
confidence: 85%
See 3 more Smart Citations
“…Under these conditions, the supercoiled DNA changed to open circular form at 24 h. After a further increase of the metal ion concentration, at 1:2 protein-to-Zn 2+ molar ratio, the catalytic activity is completely inhibited. Our previous studies showed that the CD spectra of apo NColE7 shifted slightly upon binding the Zn 2+ ion, as a consequence of minor changes in the solution structure [73] and the addition of Zn 2+ ions to N4-ZF-C105 AN resulted in a spectral shift, similar to that observed for NColE7 itself [77]. The above cataytic results using C45-ZF-N85 are in agreement with these observations.…”
Section: Plasmid Cleavage Activity Of the C45-zf-n85 Artificial Nucleasesupporting
confidence: 85%
“…This is a positive intramolecular allosteric activation process. As mentioned earlier, the NX-ZF-CY (where NX is the N-terminal segment and CY is the C-terminal segment of NColE7 with X and Y referring to the number of residues involved, respectively) type ANs could achieve specificity and moderate activity, but the regulation was only slightly functional [77]. Therefore, our goal was to develop a regulated zinc finger nuclease in which the nuclease domain itself is inactivated in the absence of a specific DNA target sequence.…”
Section: Particle Charge Detectionmentioning
confidence: 87%
See 2 more Smart Citations
“…ligand or metalbinding regulatory sequences or an endonuclease catalytic domain) linked to ZF proteins, thereby providing an opportunity to generate artificial transcription factors or enzymes for specific DNA actions. 2,[15][16][17][18][19][20][21][22][23][24][25] Previously we reported on Ni(II)-induced peptide bond hydrolysis that occurs at the N-terminal side of Ser or Thr residues in peptides, [26][27][28][29][30][31][32][33][34][35][36] designed recombinant proteins 37,38 and flexible regions of native proteins 37,39 bearing X-(Ser/Thr)-X-His-X sequences (X being any amino acid except for Cys or Pro before or after Ser/Thr). The method found application in the affinity tag removal from fusion proteins by Ni(II) ions.…”
Section: Introductionmentioning
confidence: 99%